The Vital Impact of Exercise: Fostering Health and Well-Being in Preschool Children - Seytmuratova Venera Shimbergenovna (Genius Journals, 2023)
This comprehensive article explores the multifaceted effects of exercise on the health and well-being of preschool children, emphasizing physical, cognitive, social, and emotional development. It delves into the significance of various physical activities, the role of parental involvement, and the impact on sleep patterns, fostering a holistic understanding of the benefits of exercise during early childhood
Keywords: Preschool Children; Exercise; Physical Development